PELAYANAN PROGRAM PENDAFTARAN MANDIRI AKTA TANAH (PERMATA) OLEH KEMENTERIAN AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL (ATR/BPN) KANTOR PERTANAHAN KOTA PEKANBARU - Rifky Dyan Nugroho; Febri Yulliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The current research was conducted based on the phenomenon of the new program run by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) at Land Office in Pekanbaru. It showed that the program called as Independent Registration of Land Title Deed (PERMATA) is very beneficial for Land Deed Official (PPAT) in accelerating the clearance of land certificate checking. Moreover, this research aims to find out the program service of Independent Registration of Land Title Deed (PERMATA) by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) at Land Office in Pekanbaru, as well as to find out the obstacle factors. The concept of the theory used in the research is purposed by Widodo, which lay in the indicators of service procedures in the research, the time of completion, the cost of services, product services, infrastructures, and subject competencies. Additionally, this research was carried out under qualitative descriptive design. In collecting the data, it was done through observations, interviews, as well as documentations. Then, after all of this information were collected, they would be analyzed, and studied so that it became a unity. The results of the current research showed that the PERMATA Program has been running very well. This program was a form of service which was done in order to check the land certificates by using online application. Furthermore, this PERMATA program was very helpful for the Land Deed Official (PPAT) in the managing matters related to land certificate checking. However, it was found that there were some obstacles, such as it was difficult to log into the server occasionally and the need of some developments toward this program.Keywords : Service, PERMATA, ATR/BPN